Analisis Manajemen Proyek Ide Bisnis Pupuk Bubuk Kopi (PUBUK) - Putri1, Inda Meyllya; Sibagariang, Michael Iken Bonar Anju; Mey, Nabila Arinov; Kusumo, Pradino; Hutagalung, Rince Monica; Mahendra, Rizky Adi; Christiarini, Renny (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2023)
This article was written to design a social-based business idea project that creates organic fertilizer products from processed coffee grounds. Seeing the trend of increasing consumption of coffee drinks in various circles encourages business opportunities for coffee shop businesses, especially in Batam City. The waste generated by the coffee shop is coffee grounds from the brewing process which will be disposed of after the product extraction process. Coffee grounds are known to have benefits as plant fertilizer. The result of this business idea design is a product called PUBUK (Pupuk Powder Kopi). The research method applied in writing this article is a qualitative research method, the data used is in the form of descriptive and narrative which is processed into a narrative form, as well as the data analysis technique used in this study, namely inductive data analysis. The results of this research are that the PUBUK project has succeeded in creating organic fertilizer products. This project has fulfilled the three variables contained in the Project Management Triangle, namely time, cost, and scope to produce good quality products. The next stage that needs to be carried out in this project is sustainable marketing related to PUBUK products on social media.